2009
DOI: 10.1523/jneurosci.0400-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Somatotopic Organization of Gentle Touch Processing in the Posterior Insular Cortex

Abstract: A network of thin (C and A␦) afferents relays various signals related to the physiological condition of the body, including sensations of gentle touch, pain, and temperature changes. Such afferents project to the insular cortex, where a somatotopic organization of responses to noxious and cooling stimuli was recently observed. To explore the possibility of a corresponding body-map topography in relation to gentle touch mediated through C tactile (CT) fibers, we applied soft brush stimuli to the right forearm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
151
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 238 publications
(177 citation statements)
references
References 52 publications
13
151
2
2
Order By: Relevance
“…Since this pathway is similar to that of visceral afferents, CT afferents have more in common with interoceptive systems conveying information about body state regulation than with classical exteroceptive systems conveying discriminative aspects of touch (Björnsdotter et al, 2010). The CT afferent pathway projection to insular cortex in humans is supported by neuroimaging studies of both patients and healthy controls, demonstrating that brushing stimulation likely to elicit CT discharge results in activation of contralateral mid-and posterior insular cortex (Olausson et al, 2002(Olausson et al, , 2008aBjörnsdotter et al, 2009Björnsdotter et al, , 2010. In the present study, the felt and seen velocity-specific activations in experiments 1 and 2 fell in granular insular cortex (Ig2 of Kurth et al, 2010b) on or near the long gyri and within the insular central sulcus, sometimes extending onto the posterior short gyrus.…”
Section: Affective Touch and Ct Afferent Pathwaymentioning
confidence: 91%
See 3 more Smart Citations
“…Since this pathway is similar to that of visceral afferents, CT afferents have more in common with interoceptive systems conveying information about body state regulation than with classical exteroceptive systems conveying discriminative aspects of touch (Björnsdotter et al, 2010). The CT afferent pathway projection to insular cortex in humans is supported by neuroimaging studies of both patients and healthy controls, demonstrating that brushing stimulation likely to elicit CT discharge results in activation of contralateral mid-and posterior insular cortex (Olausson et al, 2002(Olausson et al, , 2008aBjörnsdotter et al, 2009Björnsdotter et al, , 2010. In the present study, the felt and seen velocity-specific activations in experiments 1 and 2 fell in granular insular cortex (Ig2 of Kurth et al, 2010b) on or near the long gyri and within the insular central sulcus, sometimes extending onto the posterior short gyrus.…”
Section: Affective Touch and Ct Afferent Pathwaymentioning
confidence: 91%
“…CT units showed a unique preference for speeds of 1-10 cm/s, with the biggest difference between 3 and 30 cm/s, the velocities used in the present study. The CT pathway associated with dynamic, affective touch differs anatomically and functionally from that of myelinated A␤ afferents associated with rapid sensory-discriminative tactile processing (Essick et al, 1999(Essick et al, , 2010Olausson et al, 2002Olausson et al, , 2008aOlausson et al, ,b, 2010McGlone et al, 2007;Guest et al, 2009;Löken et al, 2009;Björnsdotter et al, 2009; McGlone and Spence, 2010; Morrison et al, 2010Morrison et al, , 2011. CT receptors are found in hairy but not in glabrous (smooth, e.g., palm) skin (Johansson and Vallbo, 1979;Nordin, 1990;Vallbo et al, 1999; Figure 2.…”
Section: Affective Touch and Ct Afferent Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, two distinct neural systems can be identified regarding the processing of cutaneous information. An exteroceptive modality in the somatosensory cortices is mainly involved in the discrimination of the physical characteristics of tactile stimuli, whereas an interoceptive modality in posterior insular cortex is believed to process the internal affective feeling states evoked by experienced touch (Björnsdotter, Löken, Olausson, Vallbo, & Wessberg, 2009;Craig, 2002;Olausson et al, 2002;Servos, Lederman, Wilson, & Gati, 2001;Schnitzler & Ploner, 2000). A modulation of the activation of somatosensory cortices by the observation of othersʼ affective tactile experiences is found, in particular, by studies that required explicit processing of the sensory-discriminative aspects of the visual stimuli, mostly depicting intense or painful tactile stimulation, or measured sensory-evoked potentials (e.g., Bufalari, Aprili, Avenanti, Di Russo, & Aglioti, 2007;Cheng et al, 2007;Lamm, Nusbaum, Meltzoff, & Decety, 2007), whereas no studies reported evidence for involvement of posterior insular cortices.…”
Section: Introductionmentioning
confidence: 99%